Enhancing Language Learning and Acquisition by Implementing Extensive Reading - Rojas Ugalde, Ana (2021)
An explanation is provided of how extensive reading was used in the second-year reading courses in two majors—the Teaching of English as a Foreign Language (Bachillerato en la Enseñanza del Inglés, BEI) and English as a Foreign Language (Bachillerato en Inglés, BI), both of the Universidad Nacional (Heredia, Costa Rica)—to improve their language proficiency. To implement this, the time and activities were organized in student-centered sessions so that the learners could select readings for their individual use.